I stormens öga: Veganrörelsen och motståndets metaforer - Abnersson, Veronica (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
In September 1994 an intense media debate started in Sweden about a group of young people — the vegans. In Umeå, as well as in other Swedish cities, the vegans are known as animal liberators and participants in a new kind of social and political movement. They are also known as a group who have replaced all meat, as well as other animal products, in their food with different kinds of vegetables. In the vegans interpretation of meat, it becomes a metaphor for death, war, evil, power and inequality between species, sexes and races. This kind of demonstration is a symbolic act which strengthens their critique of civilization. In their critique they use food, and especially the refusal of meat, as an important symbol of identification both within the group and as a marker outwards. In this way they struggle for a healthier ecological environment and a better world for the animals — and people — to live in. Their sometimes brutal methods and actions have become widely known and have placed Umeå on the international map.